The molecular characterization of seven novel GLI family zinc finger 3 (GLI3) variants in Chinese families with limb malformations - Tao, Siyuan; Gu, Xuyu; Wang, Xiaodong; Shen, Xiaofang; Zhao, Xiuli (Frontiers in Genetics, 2025)
BackgroundGLI family zinc finger 3 (GLI3) is a transcription factor involved in limb development. GLI3 gene variants have been shown to be associated with several human congenital limb malformations, including Greig cephalopolysyndactyly, Pallister–Hall syndrome, non-syndromic postaxial polydactyly (PAP-A/B), and preaxial polydactyly type IV (PPD-IV). The aim of this study was to identify GLI3 gene variants in ten Chinese families with limb malformations.MethodsTen Chinese families with limb malformations were recruited. Variant screening in probands was then performed using NGS, with candidate pathogenic variants verified by polymerase chain reaction (PCR) combined with Sanger DNA sequencing. Variant pathogenicity was evaluated using bioinformatics, evolutionary conservation, and disease and mutant allele co-segregation approaches. The biological effects of missense variants were predicted by three-dimensional protein conformation analysis.ResultsTen GLI3 variants were identified: two missense variants c.1063G>A (p.Val355Ile) and c.1489C>A (p.Leu497Ile), four nonsense variants c.2374C>T (p.Arg792*), c.2008C>T (p.Gln670*), c.1096 C>T (p.Arg366*), and c.2029C>T (p.Gln677*); three frameshift variants c.600delC (p.Tyr200*), c.1880_1881del (p.His627Argfs*48), and c.811_812delCT (p.Leu271Serfs*5); a large fragment deletion of NC_000007.14: g.42061081_42069739. Seven of these ten variants have never been recorded in the Human Gene Variant Database.ConclusionTen GLI3 variants were successfully identified in families with different limb malformations, indicating significant clinical and allelic heterogeneity of GLI3-related limb malformations. The present study expands the spectra of pathogenic variants and clinical manifestation for GLI3-related morphological disorder and provides solid evidence for genetic counseling and prenatal gene diagnosis in the affected families.